2020
DOI: 10.1186/s13287-020-01888-0
|View full text |Cite
|
Sign up to set email alerts
|

Short-wave enhances mesenchymal stem cell recruitment in fracture healing by increasing HIF-1 in callus

Abstract: Background As a type of high-frequency electrotherapy, a short-wave can promote the fracture healing process; yet, its underlying therapeutic mechanisms remain unclear. Purpose To observe the effect of Short-Wave therapy on mesenchymal stem cell (MSC) homing and relative mechanisms associated with fracture healing. Materials and methods For in vivo study, the effect of Short-Wave therapy to fracture healing was examined in a stabilized femur fracture model of 40 SD rats. Radiography was used to analyze the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Further study revealed that compared with siLncRNA TUG1 and miR-221-3p overexpression groups, the Bcl-2 level in the LncRNA TUG1 group was higher, with remarkably lower SDF-1 level in the miR-221-3p overexpression group than those in the control, miRNA-NC, and LncRNA TUG1 groups. SDF-1, a part of the α chemokine family, whose specific receptor CXCR4 is expressed on the surface of many cells, and the two can constitute the SDF-1/CXCR4 axis, serving as a key part in tissue injury and bone damage repair [21][22][23]. Clinical studies have shown that the secretion of SDF-1 in the bone repair site increases, and CXCR4 +-committed stem cells around bone marrow, peripheral circulating blood, and soft tissue of bone trauma migrate to the bone injury site along the gradient of SDF-1 concentration to participate in bone healing [24].…”
Section: Discussionmentioning
confidence: 99%
“…Further study revealed that compared with siLncRNA TUG1 and miR-221-3p overexpression groups, the Bcl-2 level in the LncRNA TUG1 group was higher, with remarkably lower SDF-1 level in the miR-221-3p overexpression group than those in the control, miRNA-NC, and LncRNA TUG1 groups. SDF-1, a part of the α chemokine family, whose specific receptor CXCR4 is expressed on the surface of many cells, and the two can constitute the SDF-1/CXCR4 axis, serving as a key part in tissue injury and bone damage repair [21][22][23]. Clinical studies have shown that the secretion of SDF-1 in the bone repair site increases, and CXCR4 +-committed stem cells around bone marrow, peripheral circulating blood, and soft tissue of bone trauma migrate to the bone injury site along the gradient of SDF-1 concentration to participate in bone healing [24].…”
Section: Discussionmentioning
confidence: 99%
“…The repair of bone defects requires recapitulation of complex signaling cascades, including a series of spatiotemporal angiogenesis and osteogenesis ( 34 , 35 ). However, for osteoporosis, the bone resorption rate is greater than that of new bone formation, with a decreased ability for new bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Bone defect repair is a complex signaling cascade involving spatiotemporal osteogenesis and angiogenesis, both of which require stem/progenitor cell migration and osteogenic differentiation, accompanied by ordered angiogenesis. , Exogenous osteogenic and angiogenic stimulating factors may cause imbalance in bone formation, leading to excessive bone formation or vascular leakage, and even the risk of tumor . Therefore, there is a need to increase osteogenesis and angiogenesis through potential, endogenous, and balanced stimulation.…”
Section: Discussionmentioning
confidence: 99%